TIKTOK ACCOUNT BRANDING TECHNIQUE FOR MONETIZATION - Diana Novita; Pratiwi, Pratiwi; Moch Maulana Anton (International Journal of Social Science, 2023)
Right now, surfing social media has gotten to be an auxiliary require in way of life. Right now, numerous individuals like Tiktok social media since this social media could be a. media that presents audio and visual substance. Right now, TikTok isn't as it were utilized to appear engaging substance, but there's moreover a parcel of instructive substance and indeed promoting promotions for items. So that each substance we transfer on TikTok can get great engagement to monetize our TikTok account, we got to brand it or construct our claim individual branding. There are certain ways to construct individual branding . For illustration, building account character, making unique substance and numerous others. Making unique substance implies making substance absolutely from your claim work, not plagiarizing or replicating other people's work. Indeed in the event that we copy at that point apply the ATM show, watch impersonation and adjustment. This ATM show can moreover be categorized as unique substance. The point of the inquire about is to decide the utilize of Tik Tok as individual branding. The inquire about employments subjective strategies with a graphic approach. The inquire about employments subjective strategies with a graphic approach. The comes about of the investigate are to discover out the comes about of actualizing individual branding built by substance makers on TikTok